High prevalence of hepatitis E antibodies in pregnant Egyptian women - Stoszek, Sonia K; Abdel-Hamid, Mohamed; Saleh, Doa'a A; El Kafrawy, Sherif; Narooz, Shaker; Hawash, Yousry; Shebl, Fatma M; El Daly, Mai; Said, Ahmed; Kassem, Enas; Mikhail, Nabiel; Engle, Ronald E; et al. (Transactions of the Royal Society of Tropical Medicine and Hygiene, 2006)
The epidemiology of hepatitis E virus (HEV), an enterically-transmitted cause of acute viral hepatitis (AVH), is not fully understood. During outbreaks on the Indian subcontinent and elsewhere, HEV causes severe AVH with mortality rates around 20% during pregnancy. In Egypt, where prevalence of HEV antibodies (anti-HEV) in rural communities is very high, severe HEV-caused AVH in pregnant women has not been reported. This study examined a cohort of 2,428 pregnant women in the Nile Delta to assess prevalence of, and risk factors for, anti-HEV and correlated these with history of liver disease. Anti-HEV prevalence was 84.3%. Several risk factors associated with anti-HEV included older age, many siblings, not using soap to wash produce and frequent contact with cats. History of jaundice and liver disease was rare and not increased in those having anti-HEV. Our results confirm Egypt's high HEV endemicity and show that almost all women of childbearing age in these communities had prior HEV exposures without a history of liver disease. Reasons for the lack of clinical hepatitis remain unclear but could be the result of early childhood HEV exposures, producing long-lasting immunity and/or modify subsequent responses to exposure. Alternatively, the predominant HEV strain(s) in Egypt are less virulent than those in South Asia.